Suppressor of cytokine signaling 2-12 regulates antimicrobial peptides and ecdysteroid signaling pathways in Bombyx mori (Dazao). (November 2017) - Abbas, Muhammad Nadeem; Zhu, Bao-Jian; Kausar, Saima; Dai, Li-Shang; Sun, Yu-Xuan; Tian, Ji Wu; Liu, Chao-Liang
Graphical abstract: Highlights: A BmSOCS2-12 gene was first identified from B. mori (Dazao). BmSOCS2-12 mRNA in hemocyte and fat body was upregulated when challenged by pathogens. BmSOCS2-12 could negatively regulate the expression of antimicrobial peptides. BmSOCS2-12 was involved in the regulation of ecdysteroid signaling transduction. Abstract: Suppressors of cytokine signaling (SOCS) are a potent negative regulator of diverse cytokine-related responses to maintain various physiological processes in animals. Here, we obtained the SOCS2-12 gene sequence of Bombyx mori (Dazao) ( BmSOCS2-12 ) from the National Center for Biotechnology Information (NCBI) to study its expression profile in different tissues, as well as in the immune tissues following larval exposure to pathogens. Further, we investigated the role of BmSOCS2-12 in producing antimicrobial peptides (AMPs) and as a regulator of ecdysteroid signaling transduction. The quantitative real-time PCR analysis revealed unequal transcript levels of BmSOCS2-12 in the different tissues, however the gene's expression was highest in those of fat body and hemocyte. The challenge with pathogens significantly upregulated the transcript level of BmSOCS2-12 in both fat body and hemocyte when compared with the control. By contrast, recombinant BmSOCS2-12 protein injections strongly suppressed the expression of AMPs, while the knockdown of BmSOCS2-12 by double-stranded RNA enhanced their production. Administration of 20-hydroxyecdysone significantly downregulated the BmSOCS2-12 expression in fat body, and the depletion of BmSOCS2-12 enhanced the transcript levels of 20-hydroxyecdysone-responsive genes at 48 h. Altogether, BmSOCS2-12 may have multiple functional roles in the physiology of B. mori (Dazao), since it negatively regulates the expression of AMPs and ecdysteroid signaling transduction.